2013
DOI: 10.1161/circoutcomes.111.000066
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Safety Implications of Introducing Fast Tracking in Congenital Heart Surgery

Abstract: Background-The feasibility of fast-tracking children undergoing congenital heart disease surgery has not been assessed adequately. Current knowledge is based on limited single-center experiences without contemporaneous control groups. Methods and Results-We compared administrative data for atrial septal defect (ASD) and ventricular septal defect (VSD) surgeries in children 2 months to 19 years of age at the Mount Sinai Medical Center (MSMC) with data from comparable patients at 40 centers contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Numerous studies have observed median hospitalization stay lengths for children with ASDs ranging from 3 to 6 days (Hughes et al, 2002;Thomson et al, 2002;Pasquali et al, 2011;Lawrence et al, 2013), which is in line with the 3-day LOS in the present study. Elsewhere researchers have noted comparable LOS for various heart defects, VSD (5 days in Texas, 5-6 days in other U.S. samples and 7-11 in China) (Pasquali et al, 2011;Liu et al, 2012;Lawrence et al, 2013); ToF (Texas 7, elsewhere 3-17) (Pasquali et al, 2011;Peterson et al, 2013a); HLHS (Texas 12, elsewhere 9-28) (Dean et al, 2011;Peterson et al, 2013a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Numerous studies have observed median hospitalization stay lengths for children with ASDs ranging from 3 to 6 days (Hughes et al, 2002;Thomson et al, 2002;Pasquali et al, 2011;Lawrence et al, 2013), which is in line with the 3-day LOS in the present study. Elsewhere researchers have noted comparable LOS for various heart defects, VSD (5 days in Texas, 5-6 days in other U.S. samples and 7-11 in China) (Pasquali et al, 2011;Liu et al, 2012;Lawrence et al, 2013); ToF (Texas 7, elsewhere 3-17) (Pasquali et al, 2011;Peterson et al, 2013a); HLHS (Texas 12, elsewhere 9-28) (Dean et al, 2011;Peterson et al, 2013a).…”
Section: Discussionsupporting
confidence: 91%
“…Elsewhere researchers have noted comparable LOS for various heart defects, VSD (5 days in Texas, 5-6 days in other U.S. samples and 7-11 in China) (Pasquali et al, 2011;Liu et al, 2012;Lawrence et al, 2013); ToF (Texas 7, elsewhere 3-17) (Pasquali et al, 2011;Peterson et al, 2013a); HLHS (Texas 12, elsewhere 9-28) (Dean et al, 2011;Peterson et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…We were also able to assess complications specific to congenital heart surgery. [3][4][5][6][7] Standardized information collected across hospitals within the PHIS Database allowed calculation of total hospital costs, which better estimate the resources consumed to carry out the service provided, compared with charge data reported in previous studies, which only reflect what the hospital billed for a service, may vary across hospitals, and overestimate cost. 6,7 These types of data linkages can maximize the strengths and mitigate the weaknesses of each data set, and allow for analyses not possible within each individual data set alone.…”
Section: Discussionmentioning
confidence: 99%
“…A previous single center report demonstrated that LOS (and associated hospital costs) could be reduced by standardization of care involving practices aimed at early extubation and mobilization in children undergoing certain types of heart surgery. 5 In adult surgical subspecialties, multicenter quality improvement collaboratives have proven to be successful models for sharing these types of best practices across hospitals, and reducing variation in clinical outcomes and costs. [31][32][33] A regional collaborative in Michigan is estimated to reduce complications after general and vascular surgery in ∼2500 patients each year, translating into annual savings of ∼$20 million.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation